The potential of a free pedometer mobile application in assessing physical activity status and its association with body composition among International Islamic University Malaysia (IIUM) students. - Mohd Shukri, Nor Azwani; Che Ku Aziz, Che Ku Nur Aishah; Muhd Noor, Izzah Atirah (2019)
Objective: Many young people nowadays have sedentary lifestyle which might contribute to obesity prevalence. With the technology advancement, free mobile applications (apps) are now available to assist them to be more physically active. Thus this study aimed to determine: i) the relative agreement between an objective assessment (pedometer app) and a conventional self-reported method (International Physical Activity Questionnaire, IPAQ) in determining physical activity (PA) status, and ii) the association between step counts and body composition. Methodology: IIUM Kuantan Campus students (n= 86) aged 18 to 27 years were recruited using convenient sampling. Anthropometric measurements including height, weight and body composition were taken using SECA stadiometer and OMRON body fat analyzer. Participants were requested to use a free-of-charge mobile pedometer app (Accupedo Pedometer) and the IPAQ to record their PA over three days (two weekdays and one weekend day). Classification of the PA status based on pedometer and IPAQ were referred to Basset (2004) and IPAQ (2005), respectively. Relative agreement between both data were analyzed using Kappa statistics, cross-classification, and Pearson correlation. Results and Discussion: It was found that 74% (based on IPAQ) and 91% (based on pedometer app) of the participants were categorized as low active. The Kappa value was k=0.126 (p=0.016) indicating a slight but significant agreement between these two methods. Cross-classification demonstrated that ~40% (n=34) of the participants were correctly classified into the same third whereas ~16% (n=14) were grossly misclassified. In addition, the average steps count perday (by pedometer app) was significantly correlated (r=0.235, p=0.03) with total MET-minutes/week (by the IPAQ). However, no association between steps count and BMI or percent body fat was found. Conclusion: The pedometer app was comparable to the self-reported IPAQ in assessing PA status. This shows that a cost-free and convenient mobile app is applicable to be used for daily PA assessment among young people.